2007
DOI: 10.1093/toxsci/kfm263
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular System as a Target of Metal Toxicity

Abstract: Vascular system function involves complex interactions among the vascular endothelium, smooth muscle, the immune system, and the nervous system. The toxic metals cadmium (Cd), arsenic (As), and lead (Pb) can target the vascular system in a variety of ways, ranging from hemorrhagic injury to subtle pathogenic remodeling and metabolic changes. Acute Cd exposure results in hemorrhagic injury to the testis, although some strains of animals are resistant to this effect. A comparison of Cd-sensitive with Cd-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
172
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(180 citation statements)
references
References 124 publications
4
172
0
4
Order By: Relevance
“…4 In addition, in human lymphocytes, elevated lead concentrations with protein denaturation were also found in our studies. 4 This is in concordance with the study from Prozialeck et al 5 showing the vascular system as a target of lead toxicity.…”
Section: Lead Smoking and Peripheral Vascular Functionsupporting
confidence: 87%
“…4 In addition, in human lymphocytes, elevated lead concentrations with protein denaturation were also found in our studies. 4 This is in concordance with the study from Prozialeck et al 5 showing the vascular system as a target of lead toxicity.…”
Section: Lead Smoking and Peripheral Vascular Functionsupporting
confidence: 87%
“…There is considerable public health interest in the possible toxic effects of environmental lead exposure on the cardiovascular system, with additional concern regarding the role of chronic low-level lead exposures in the pathogenesis of hypertension, a leading risk factor for cardiovascular disease morbidity and mortality [7,2]. Vupputuri et al, [22] suggested that increased levels of B-Pb remain an important environmental risk factor for elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been detected in all phases of environment and biological system. The persistence of lead in the blood of animals and humans and the associated health risk is a topic of current debate and concern [1,2]. Moreover, rapid industrialization and the continued use of leaded gasoline appear to be increasing lead exposure throughout the developing world [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly affected organ systems are the kidney, lung, bone and skeletal, cardiovascular, and nervous systems (Jaishankar et al 2014). Observational studies indicate that chronic Cd exposure is associated with an increased risk of cardiovascular disease, including hypertension, atherosclerosis, nephropathy, and diabetes (Puri 1999;Satarug et al 2005;Eum et al 2008;Prozialeck et al 2008;Messner and Bernhard 2010;Alissa and Ferns 2011;ATSDR 2012;Satarug and Moore 2012).…”
Section: Introductionmentioning
confidence: 99%